2020
DOI: 10.1002/smtd.202000567
|View full text |Cite
|
Sign up to set email alerts
|

Semimetal 1H‐SnS2 Enables High‐Efficiency Electroreduction of CO2 to CO

Abstract: Transition metal dichalcogenides (TMDs) are a series of outstanding 2D materials for various electrocatalytic reactions due to their unique variety of atomic configurations and band structures, such as MoS 2 and WS 2. [1-4] They exist in different crystal phases, such as the stable phase (2H) and metastable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 57 publications
(83 reference statements)
1
23
1
Order By: Relevance
“…S7), which clearly showed that CoFe-LDH/HP had the lower interfacial charge-transfer resistance than CoFe-LDH/SP. Further, the obtained Tafel slope of CoFe-LDH/HP is close to a theoretical value (118 mV dec −1 ), which indicates that the first single-electron transfer from CO 2 to produce *COOH moiety is the ratedetermining step (RDS) for the CO 2 RR on CoFe-LDH/HP [48,49].…”
supporting
confidence: 74%
“…S7), which clearly showed that CoFe-LDH/HP had the lower interfacial charge-transfer resistance than CoFe-LDH/SP. Further, the obtained Tafel slope of CoFe-LDH/HP is close to a theoretical value (118 mV dec −1 ), which indicates that the first single-electron transfer from CO 2 to produce *COOH moiety is the ratedetermining step (RDS) for the CO 2 RR on CoFe-LDH/HP [48,49].…”
supporting
confidence: 74%
“…According to the gross-margin model, formate is considered to be one of the most economically feasible products in the CO 2 RR, which can be widely used as an important raw material in the chemical and pharmaceutical industries, as well as a potential hydrogen carrier and the liquid fuel for proton-exchange membrane fuel cell [4][5][6]. Up to now, various metal-based electrocatalysts, such as Pd, In, Hg, Pb, Cd, and Sn, have been exploited to achieve the CO 2 electroreduction to formate [7][8][9][10][11][12][13]. Among these electrocatalysts, Sn-based materials have attracted considerable attention due to their advantages of earth abundance, non-toxicity, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…The whole XPS spectrum of pure SnS 2 , SnS 2 -Pt-3 and SnS 2 -Pt-4 is shown in Figure S3a The X-ray photoelectron spectroscopy (XPS) was used to determine the elemental composition of SnS2 nanosheets doped with different proportions of Pt precursor. As shown in the high-resolution XPS spectra of pure SnS2 in Figure S2a,b, the two main peaks of Sn are 3d5/2 of 486.9 eV and 3d3/2 of 495.3 eV are in line with Sn 4+ , and the two main peaks of S are 2p3/2 of 162.0 eV and 2p1/2 of 163.2 eV are assigned to S 2− , respectively [38]. By analyzing the distribution of Sn, S elements and the ratio of Sn/S (1:2) in the EDS mapping (Table S2) and the XRD diagram ( Figure S2f), indicating that suggesting a rational stoichiometric composition of SnS2.…”
Section: Resultsmentioning
confidence: 91%